THE ROLE OF INTERNAL AUDIT ON THE PERFORMANCE EFFECTIVENESS OF PUBLIC SECTOR ORGANIZATIONS - Irwansyah; Awaludin Malik, Sonya; Patmawati Kusumawardani, Yulia; Kusumah, Megasari; Oki Dewa Brata, Ignatius (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the role of Internal Audit on organizational performance effectiveness. The factors tested in this study are internal audits as independent variables and organizational performance as dependent variables. The research methods used are quantitative. The population of this study is all employees of Yayasan Mandiri Daya Insani Jln. Kayu Agung II No. 5. RT 07/04 Bandung. The data collection techniques used in this research are included in the primary data obtained from the dissemination of the questionnaire to all employees of Yayasan Mandiri Daya Insani with a sample number of 49 respondents. While the method of analysis used in this research is simple linear regression analysis. On the level of significance of 5%. Based on the research results shows that Internal Audit has a strong relationship with the effectiveness of organizational performance. While the magnitude of the Internal Audit role for organizational performance effectiveness is 36.3% while the remaining 63.7% is the influence of other factors outside the Internal Audit role variables.